1998
DOI: 10.1038/sj.sc.3100611
|View full text |Cite
|
Sign up to set email alerts
|

A study of the origin of the electric activity of the rectum: Is it neurogenic or myogenic?

Abstract: The rectum possesses electric activity, the origin of which is yet undetermined. The current study investigates the possible source of these waves. Three electrodes were sutured serially to the serosal surface of the rectum in 10 dogs. The rectal pressure was measured by a perfused catheter. Simultaneous recordings of the electric activity and rectal pressure were done before and after bilateral pelvic ganglionectomy and rectal myotomy. Regular slow waves or pacesetter potentials (PPs) followed by inconsistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 3 publications
3
20
1
Order By: Relevance
“…The rectal pressure elevation in association with APs is in accord with previous studies (Shafik, 1993b(Shafik, , 1994(Shafik, , 1998. These studies have also shown that the frequency and amplitude of the APs as well as the concomitant rectal pressure elevation increased with increase of the rectal distending volume.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The rectal pressure elevation in association with APs is in accord with previous studies (Shafik, 1993b(Shafik, , 1994(Shafik, , 1998. These studies have also shown that the frequency and amplitude of the APs as well as the concomitant rectal pressure elevation increased with increase of the rectal distending volume.…”
Section: Discussionsupporting
confidence: 90%
“…Preceding studies (Shafik, 1993b(Shafik, , 1994(Shafik, , 1998Shafik et al, 1999), have suggested the presence of a rectosigmoid pacemaker which seems to initiate the rectal electric activity. The current study has shown that the waves spread caudad along the rectal longitudinal muscle coat.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent study of the rectal electric activity was done to investigate whether the origin of these waves is neurogenic or myogenic (26), and it was suggested that these waves are not initiated by, but may be under the control of, the extrarectal autonomic innervation.…”
Section: Resultsmentioning
confidence: 99%
“…The electric waves seem generated by the interstitial cells of Cajal (ICCs) and mediate the contractile activity of the smooth musculature [5,7,11,12]. Meanwhile, the contraction of the prostatic smooth fibers may be responsible for the urethral pressure increase associated with the APs [10].…”
mentioning
confidence: 99%